Chemotherapeutic potential of quercetin on human bladder cancer cells. Issue 9 (28th July 2016) - Oršolić, Nada; Karač, Ivo; Sirovina, Damir; Kukolj, Marina; Kunštić, Martina; Gajski, Goran; Garaj-Vrhovac, Vera; Štajcar, Damir
ABSTRACT: In an effort to improve local bladder cancer control, we investigated the cytotoxic and genotoxic effects of quercetin on human bladder cancer T24 cells. The cytotoxic effect of quercetin against T24 cells was examined by MTT test, clonogenic assay as well as DNA damaging effect by comet assay. In addition, the cytotoxic effect of quercetin on the primary culture of papillary urothelial carcinoma (PUC), histopathological stage T1 of low- or high-grade tumours, was investigated. Our analysis demonstrated a high correlation between reduced number of colony and cell viability and an increase in DNA damage of T24 cells incubated with quercetin at doses of 1 and 50 µM during short term incubation (2 h). At all exposure times (24, 48 and 72 h), the efficacy of quercetin, administered at a 10× higher dose compared to T24 cells, was statistically significant ( P < 0.05) for the primary culture of PUC. In conclusion, our study suggests that quercetin could inhibit cell proliferation and colony formation of human bladder cancer cells by inducing DNA damage and that quercetin may be an effective chemopreventive and chemotherapeutic agent for papillary urothelial bladder cancer after transurethral resection.